Penerapan Komunikasi Data Pada Osi Layer PC to PC Menggunakan Cisco Packet Tracer - Shafwan Iman Ramadhani; Ratu Farah Humainah; Aditio Nugroho; Didik Aribowo (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Data communication is a method for transferring information using an electronic transmission system from one computer device to another computer device, or from a computer to a specific terminal. The implementation of data communication in Osi Layer PC to PC aims to update the method of data communication. OSI is a reference model in the form of a conceptual framework that establishes connection standards for computers. The aim of creating the OSI reference model is to serve as a guide for users to make it easier to communicate between PCs. This research is descriptive in nature, with the aim of recognizing, observing and explaining certain phenomena without manipulation or intervention. The two methods used in this research are literature study and simulation. In this research, Cisco Packet Tracer software is used to create computer network simulations. The research results obtained are in the form of a simulation of implementing data communications using Cisco Packet Tracket from creating a network topology, determining the IP address to simulating a computer network.